Low Carbon Economy and Green Financing - William Tjong; Jessica (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Low carbon economy and Green financing need urgent actions and collaborations from all countries in the world. In 2015 United Nations call for action with the introduction of 17 Sustainable Development Goals (SDGs) and since then all countries have begun their journey to achieve the goals set by 2030. USA, EU are developed countries and market leaders in setting a high bar in progressing along the way, in contrary to developing countries. Regulations and framework in developing countries create gaps that could be easily spotted compared with developed countries. Other obstacles come from lagging in the sustainable agenda implementation in developing countries caused by combination of capabilities building, low awareness, and availability of solid framework. This research use panel unit root analysis, Johansen’s co-integration analysis and Granger causality test based on error correction model for the dataset from 1971 to 2014. The result indicates that in the short run, there is one-way causality from energy consumption to CO2 emission. While in the long run the result supports the presence of cointegration relationships between variables.